Combined transcriptomic and metabolomic analysis of phenylpropanoid biosynthesis in the mechanism of leaf angle formation in Sorghum - Li, Jinhong; Wang, Yiwei; Zhao, Yuche; Zhang, Yanpeng; Qu, Kuangzheng; Zhu, Zhenxing; Wang, Chunyu; Li, Zhenjun; Cong, Ling; Gang, Shuang; Lu, Xiaochun (Frontiers in Plant Science, 2025)
Leaf angle is a crucial morphological trait for improving crop architecture and facilitating high-density planting. This study aims to explore the mechanism underlying leaf angle formation in sorghum. We used the el1 mutant, generated through ethyl methane sulfonate mutagenesis in our laboratory, to conduct a comprehensive analysis, including phenotypic, cytological, and integrated transcriptomic and metabolomic studies. At the S3 stage, el1 leaves exhibited shrinkage, and their leaf angles were significantly smaller compared to those of the wild type (WT). Cytological analyses revealed that at the S1 stage, the auricles of el1 had larger cell sizes and fewer cells than those of the WT. Metabolomic analysis based on the Kyoto Encyclopedia of Genes and Genomes (KEGG) identified 19 significantly differentiated metabolites, with 10 upregulated and 9 downregulated. Transcriptomics KEGG analysis revealed 858 upregulated and 533 downregulated differentially expressed genes (DEGs). Integrated analysis highlighted that 12 DEGs were associated with trans-5-O-(p-coumaroyl)shikimate in phenylpropanoid biosynthesis, with 11 positively correlated and one negatively correlated DEG. Additionally, 43 DEGs were linked to coniferyl alcohol, with 35 positively correlated and 8 negatively correlated in el1 compared to WT. This study establishes a theoretical foundation for understanding the molecular mechanisms by which phenylpropanoid biosynthesis influences leaf angle formation in sorghum and offers a basis for optimizing plant architecture to enable high-density planting.